The role of lumbar lordosis and pelvic sagittal balance in femoroacetabular impingement. (October 2018) - Fader, R. R.; Tao, M. A.; Gaudiani, M. A.; Turk, R.; Nwachukwu, B. U.; Esposito, C. I.; Ranawat, A. S.
Abstract : Aims: The purpose of this study was to evaluate spinopelvic mechanics from standing and sitting positions in subjects with and without femoroacetabular impingement (FAI). We hypothesize that FAI patients will experience less flexion at the lumbar spine and more flexion at the hip whilst changing from standing to sitting positions than subjects without FAI. This increase in hip flexion may contribute to symptomatology in FAI. Patients and Methods: Male subjects were prospectively enrolled to the study (n = 20). Mean age was 31 years old (22 to 41). All underwent clinical examination, plain radiographs, and dynamic imaging using EOS. Subjects were categorized into three groups: non-FAI (no radiographic or clinical FAI or pain), asymptomatic FAI (radiographic and clinical FAI but no pain), and symptomatic FAI (patients with both pain and radiographic FAI). FAI was defined as internal rotation less than 15° and alpha angle greater than 60°. Subjects underwent standing and sitting radiographs in order to measure spine and femoroacetabular flexion. Results: Compared with non-FAI controls, symptomatic patients with FAI had less flexion at the spine (mean 22°, sd 12°, vs mean 35°, sd 8°; p = 0.04) and more at the hip (mean 72°, sd 6°, vs mean 62°, sd 8°; p = 0.047). Subjects with asymptomatic FAI had more spine flexion and similar hip flexion when compared to symptomatic FAI patients. Both FAI groups also sat with more anterior pelvic tilt than control patients. There were no differences in standing alignment among groups. Conclusion: Symptomatic patients with FAI require more flexion at the hip to achieve sitting position due to their inability to compensate through the lumbar spine. With limited spine flexion, FAI patients sit with more anterior pelvic tilt, which may lead to impingement between the acetabulum and proximal femur. Differences in spinopelvic mechanics between FAI and non-FAI patients may contribute to the progression of FAI symptoms. Cite this article: Bone Joint J 2018;100-B:1275–9.